2013
DOI: 10.1387/ijdb.130020re
|View full text |Cite
|
Sign up to set email alerts
|

Role of stem cell proteins and microRNAs in embryogenesis and germ cell cancer

Abstract: Embryonic stem (ES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 123 publications
(123 reference statements)
2
24
0
Order By: Relevance
“…SOX2 is expressed in pluripotent and multipotent embryonic and extra-embryonic cells [249]. However according to a number of studies SOX2 is not expressed in developing human germ cells as is the case in mice [248,250,251]. A single study showed SOX2 in normal germ cells/CIS/SE, but the authors stated that this is likely an artifact of a single antibody showing this result [252].…”
Section: Sox2 and Sox17mentioning
confidence: 99%
See 1 more Smart Citation
“…SOX2 is expressed in pluripotent and multipotent embryonic and extra-embryonic cells [249]. However according to a number of studies SOX2 is not expressed in developing human germ cells as is the case in mice [248,250,251]. A single study showed SOX2 in normal germ cells/CIS/SE, but the authors stated that this is likely an artifact of a single antibody showing this result [252].…”
Section: Sox2 and Sox17mentioning
confidence: 99%
“…A single study showed SOX2 in normal germ cells/CIS/SE, but the authors stated that this is likely an artifact of a single antibody showing this result [252]. Instead of SOX2, human germ cell progenitors express SOX17 [195,248,250] which is reflected in SOX17 expression in CIS and SE [23,24,248]. SOX17 is involved in regulating differentiation into primitive endoderm [218,253].…”
Section: Sox2 and Sox17mentioning
confidence: 99%
“…MiRNAs are incorporated into the RISC complex and base paired to the 3'-untranslated region (3' UTR) of target genes to exert their regulatory effects [7]. MiRNAs regulate several types of physiological and pathological processes, including embryogenesis, cell maintenance, lineage determination, and normal cell physiology [8,9,10,11]. Studies have also shown that miRNAs are involved in tumorigenesis and cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, over 1000 mammalian miRNAs have been discovered through cloning and sequencing approaches, which include several hundreds miRNAs in humans. miRNAs are composed of 20-22 nucleotides in length, which are processed from larger pri-miRNAs into miRNA duplexes through the cleavage of RNase III enzyme Dicer [6]. One strand of the duplex is associated with the RNA-induced silencing complex (RISC) while the other strand is universally degraded by cellular nucleases.…”
Section: Introductionmentioning
confidence: 99%
“…It is predicted that miRNAs may control the activities of more than 60% of all proteincoding genes [10,11]. Of note, miRNA-induced mRNA degradation occurs in mammals, whereas the majority of mammalian miRNAs are thought to inhibit target gene expression by a more immediate and low energy-consumption way, translational regulation, which induces rapid changes of protein synthesis without excessive transcriptional activation and subsequent steps in mRNA processing [6,[12][13][14]. In addition, translational modulation form of gene expression possesses the advantage of being readily reversible, thereby providing the cell with great flexibility in response to different cytotoxic stresses [15].…”
Section: Introductionmentioning
confidence: 99%